2014
DOI: 10.1039/c4cc02226b
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic phthalocyanine–cyclodextrin conjugates for cancer photodynamic therapy

Abstract: Three phthalocyanines (Pcs) conjugated with α-, β- and γ-cyclodextrins (CDs) were prepared and their application as photosensitizer (PS) agents was assessed by photophysical, photochemical and in vitro photobiological studies. The photoactivity of Pc-α-CD and Pc-γ-CD ensures their potential as PDT drugs against UM-UC-3 human bladder cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 27 publications
0
59
0
Order By: Relevance
“…19) for cancer PDT. 116 Three such derivatives, Pc–α-CD, Pc–β-CD and Pc–γ-CD, were synthesized via nucleophilic substitution of cyclo-maltohexaose (α-CD), cyclo-maltoheptaose (β-CD) and cyclo-maltooctaose (γ-CD) on two fluorine atoms of PcF 16 . Then, they tested these compounds on the UM-UC-3 bladder cancer cell line for phototoxicity and the results revealed that Pc–α-CD and Pc–γ-CD exhibited higher phototoxi-city compared to Pc–β-CD.…”
Section: Substituted Fluorinated Porphyrinoids For Biological Applicamentioning
confidence: 99%
“…19) for cancer PDT. 116 Three such derivatives, Pc–α-CD, Pc–β-CD and Pc–γ-CD, were synthesized via nucleophilic substitution of cyclo-maltohexaose (α-CD), cyclo-maltoheptaose (β-CD) and cyclo-maltooctaose (γ-CD) on two fluorine atoms of PcF 16 . Then, they tested these compounds on the UM-UC-3 bladder cancer cell line for phototoxicity and the results revealed that Pc–α-CD and Pc–γ-CD exhibited higher phototoxi-city compared to Pc–β-CD.…”
Section: Substituted Fluorinated Porphyrinoids For Biological Applicamentioning
confidence: 99%
“…24). All these results suggest that the higher phototoxicity of these compounds can be attributed to their higher cellular uptake and efficiency in generating intracellular ROS (Lourenço et al 2014).…”
Section: Cancer Pdt and Porphyrin-type Derivatives 1003mentioning
confidence: 81%
“…Having this in mind and in order to overcome the aggregation usually associated to these highly hydrophobic molecules, Lourenco et al reported in 2014 the synthesis of amphiphilic phatalocyanines (PCs) conjugated with α-, β-and γ-cyclodextrins as potential PSs for PDT (Lourenço et al 2014). Thus, Pc-α-CD 24, Pc-β-CD 25 and Pc-γ-CD 26 were synthesized by nucleophilic substitution of two fluorine atoms of PcF 16 (hexadecafluorophthalocyanine), a single substitution of a β-fluoro atom in one of the isoindole units followed by a second attack in another one of the adjacent isoindole unit, using, respectively, cyclo-maltohexaose (α-CD), cyclomaltoheptaose (β-CD) and cyclo-maltooctaose (γ-CD) (Fig.…”
Section: Cancer Pdt and Porphyrin-type Derivatives 1003mentioning
confidence: 99%
See 2 more Smart Citations